Aplikasi Mobile Kesehatan Maternal Menggunakan Haversine Formula Untuk Pencarian Layanan Terdekat - Khairunnisyah, Siti; Triase, Triase (JURIKOM (Jurnal Riset Komputer), 2025)
Health facilities are important facilities used to provide health services to the community. Types of public health facilities include hospitals, health centers, clinics, pharmacies, poskesdes, and pustu. Knowing the location of the nearest health facility is very important, especially in emergency situations. One effective solution to access such information is through location-based mobile applications. This study aims to build a mobile application that can help users, especially pregnant women and postpartum mothers, in finding the nearest maternal health services in Bandar District by utilizing the Haversine Formula. This formula is used to calculate the distance between the user's location and health facilities based on geographic coordinates. This application also presents an ordered list of health facilities based on the closest distance and can be filtered based on the type of service needed. Functional testing is done using the black box method which shows that all application features run well according to the design. Interim results show that the application is able to display accurate data about the position and distance of maternal health services efficiently, and get positive feedback from early users who state that the application is very helpful in urgent conditions and for routine control needs.